Pengaruh Kualitas Produk, Kualitas Layanan, dan Harga Terhadap Minat Keputusan Pembelian pada UMKM Surakarta - Ardiansyah, Gilang; Praswati, Aflit Nuryulia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the influence of product quality, service quality, and price on purchase decision interest in Micro, Small, and Medium Enterprises (MSMEs) in Surakarta. A quantitative approach was used in this research, employing purposive sampling to collect data from 200 respondents who met certain criteria: MSME customers in Surakarta aged 17-40 years who had made purchases more than twice. Primary data were collected through questionnaires based on a Likert scale and analyzed using Smart PLS version 3.0 software to perform Partial Least Square (PLS) testing. The results showed that product quality, service quality, and price significantly influence consumers' purchase decision interest. Product quality has the greatest influence on purchase decision interest, followed by service quality and price. These findings indicate that improving product and service quality, as well as setting competitive prices, can enhance consumer purchase interest in MSMEs in Surakarta. This study provides practical implications for MSMEs to focus on enhancing product and service quality and establishing effective pricing strategies to attract consumer purchase interest and decisions.